Lumbar spondylodiscitis secondary to Enterobacter cloacae septicaemia after extracorporeal shock wave lithotripsy infections [7] - Kamanli, A.; Sahin, S.; Kavuncu, V.; Felek, S. (BMJ Publishing Group, 2001)
[Abstract Not Available]
Keywords: adult; case report; Enterobacter cloacae; extracorporeal lithotripsy; hematuria; human; infection risk; intervertebral disk degeneration; letter; lumbar spine; male; nocturia; pollakisuria; priority journal; septicemia